Structural, dielectric and ferroelectric properties of lead-free Ba0.85Ca0.15Zr0.10Ti0.90O3 ceramics prepared by Plasma Activated Sintering. Issue 16 (December 2016) - Li, S.B.; Zhang, L.M.; Wang, C.B.; Ji, X.; Shen, Q.
Abstract: Lead-free Ba0.85 Ca0.15 Zr0.10 Ti0.90 O3 (BCZT) ceramics were prepared by Plasma Activated Sintering (PAS). The influence of PAS sintering temperature on the crystalline phase, microstructure, and, dielectric and ferroelectric properties of BCZT ceramics were studied. The phase structure of BCZT ceramics first changed from rhombohedral phase to the coexistence of rhombohedral and tetragonal phases and then to tetragonal phase as the sintering temperature increased. Microstructural characterization of BCZT ceramics indicated that PAS can obtain a compact microstructure at lower temperatures of 1150–1300 °C compared with that from common pressureless sintering. The BCZT ceramics showed different degrees of diffuseness with increased temperature, and the diffuseness exponents C are all approximately on the order of 10 5 °C. The dielectric and ferroelectric properties of BCZT ceramics were enhanced with increased sintering temperature. BCZT ceramics sintered at 1250 °C exhibited optimum properties of room-temperature εr =2863, εm =6650, and 2Pr =25.24 μC/cm 2, resulting from the relatively higher tetragonal phase content of the MPB between tetragonal and rhombohedral phases together with a compact microstructure.